Investigating cultural influences to privacy: case of Malaysia's computer professionals' self-regulatory efficacy concerning information privacy practices / Emely Shazwan Abdul Wahid - Abdul Wahid, Emely Shazwan (2013)
Information privacy is one of the most valuable and important element to be guarded for each individual. The importance of collecting and gathering the information about a person has become a must in most of our daily activities in recent years. There are many cases nowadays which involve the integrity of the data handler to safeguard our personal info, and not disseminating it without our consent. The objective of this research is to (1) propose conceptual framework of 'Cultural Influences to Information Privacy Self-regulatory Efficacy', and (2) investigate cultural influences to privacy by using case study of Malaysia's computer professionals' self-regulatory efficacy with information privacy practice. This research provides modest empirical contributions in order to find the relationship between Islamic culture and self-regulatory efficacy theory. By using theoretical frameworks of'Islamic Cultural Dimensions' and 'Information Privacy Self-regulatory Efficacy Dimensions', further studies have been carried out. Survey method is used for data collection and convenient sampling is used for the data sampling. The data is then analyzed using SPSS 20.0.0 and Ordinal Regression Analysis. The findings include: (1) Conceptual Framework of 'Information Privacy Self-Regulatory Efficacy Dimensions' and 'Cultural Dimensions', and (2) empirical analysis results provided a mixture of a positive and negative relationship on the culture influence to the self-regulatory efficacy towards safeguarding information privacy. The empirical result and discussion provided in this study can provide a better understanding on the culture influence towards self-regulatory efficacy of a person concerning information privacy. The identification of self-regulatory efficacy factorial structure concerning information privacy may provide contribution in future studies, which may help to determine the relationship between psychological and privacy efficacy, for instance, ethical attitude, ethical intention and self esteem. Thus, this research can be a starting point for other researchers to further conduct the studies on how different cultures in different countries influenced the self-regulatory efficacy of a person towards information privacy.